Quaternized Amphiphilic Block Copolymers/Graphene Oxide and a Poly(vinyl alcohol) Coating Layer on Graphene Oxide/Poly(vinylidene fluoride) Electrospun Nanofibers for Superhydrophilic and Antibacterial Properties - Park, Jeong-Ann; Cho, Kie Yong; Han, Chee Hun; Nam, Aram; Kim, Jae-Hyun; Lee, Sang-Hyup; Choi, Jae-Woo (Nature Publishing Group, 2019)
Poly(vinylidene fluoride) (PVDF) is common polymer for electrospinning, however, its high hydrophobicity is a major drawback, which cause fouling. To introduce hydrophilicity and antibacterial activity, quaternary ammonium-functionalized amphiphilic diblock copolymers were synthesized and blended with a PVDF/graphene oxide (GO) solution, then, electrospun and coated with a hydrophilic polymer, poly(vinyl alcohol) (PVA). The amphiphilic block copolymer, consisting of a hydrophobic poly(methyl methacrylate) block and a hydrophilic poly[N,N-2-(dimethylamino)-ethyl methacrylate) block (PMMA-b-PDMAEMA), was synthesized. Polymeric quaternary ammonium with three different alkyl chain lengths (C-2, C-4, and C-8) were successfully introduced to obtain as q-PMMA-b-PDMAEMA. The q-PMMA-b-PDMAEMA in the nanofiber matrix was confirmed by C=O bands (1734 cm(-1)) in the Fourier transform infrared spectra. Nano-sized spherical protuberances were distributed on the surface as revealed by field emission scanning and transmission electron microscopies. The PVDF/GO/q-PMMA-b-PDMAEMA@PVA nanofibers has superhydrophilic properties (water contact angle = 0-20 degrees) and the pure water flux was generally improved by increasing the alkyl chain length. When introducing the longest alkyl chain (C-8,C-OBC), the total fouling ratio was the lowest (49.99%) and the bacteria removal capacities after 60 min were the highest for both Escherichia coli (4.2 x 10(5) CFU/mg) and Staphylococcus aureus (6.1 x 10(5) CFU/mg) via growth inhibition and cytoplasmic membrane damage.